Interpreting The State's Right to Control In the provisions of Article 33 Paragraph (3), The Constitution of 1945 Republic of Indonesia - Suparto, Suparto (UIR Law Review, 2020)
Article 33 paragraph (3) of The Constitution Republic of Indonesia in 1945 stipulates that "Earth, water and natural resources contained therein controlled by the State and used for the people's welfare". Understanding of the earth (which is called land) according to the provisions of Article 1 paragraph (4) of Law Number 5 of 1960 concerning Basic Regulations on Basic Agrarian Issues is the surface of the earth and the body of the earth underneath it and which is under water. The meaning of the provisions of Article 33 paragraph (3) in The Constitution of 1945 is that the State as the highest power organization of all people (the nation) acts as the Governing Body. The right to control the State or be controlled by the State in this article does not mean "owned", but in the sense of giving authority to the State as the highest power organization of the Indonesian nation. The Constitutional Court elaborated State's Right to Control becomes 5 (five) authorities whose purpose is as much as possible for the prosperity of the people, including: (1). Formulate policy (beleid), (2). Make arrangements (regelendaad), (3). Carry out management (bestuurdaad), (4). Carry out management (beheerdaad), and (5). Supervise (toeichthoudensdaad). The earth, water and natural resources contained in the earth are the main points of people's prosperity, therefore they must be controlled by the State and used for the greatest prosperity of the people.